Financial Performance Analysis of PT. Industri Jamu and Farmasi Sido Muncul Tbk. after the Initial Public Offering (IPO) and the Influence Toward Profit Growth - Widyastuti, Linda -; Zaenuddin, Achmad -; Suratno, Agus - (Politeknik Negeri Semarang, 2020)
The aim of this study was to analyze the financial performance of PT. Industri Jamu and Farmasi Sido Muncul Tbk. after conducted the Initial Public Offering (IPO) period of 2014 - 2018 and its influence toward the profit growth. Multiple Linear Regression Analysis method by SPSS 25Â was used in this study equipped with the Classic Assumption Test and Coefficient of Determination to analyze the influence of current ratio (X1), debt to asset ratio (X2), total asset turnover ratio (X3), return on equity (X4), and earning per share (X5) as independent variables on profit growth as dependent variable. The data were secondary data obtained from the annual report and financial report of PT Industri Jamu andÂ Farmasi Sido Muncul.The result showed that overall the financial performance of PT Industri Jamu and Farmasi Sido Muncul Tbk. after the IPO was in good condition even though fluctuated. Meanwhile, the multiple linear regression analysis results showed that partially, the variable of total asset turnover ratio has positive significant and earning per share has a negative significant influence on profit growth. However, the other variables have an insignificant influence on profit growth. On the other hand, Simultaneously all of the independent variables significantly influence profit growth.